99mTc-MIBI single-photon emission-computed tomography in diagnosis of lung cancer and mediastinal metastasis lymph nodes. - Shen-tu Yang; Zhou Yun-zhong; Zeng Jun (Acta Pharmacologica Sinica, 2016)
AIM: To evaluate the value of technetium-99m-methoxyisobutyl isonitrile (99mTc-MIBI) single-photon emission-computed tomography (SPECT) in diagnosis of lung cancer and in preoperative prediction of mediastinal metastasis lymph nodes. METHODS: After the chest image of 99mTc-MIBI SPECT, fifty patients (40M, 10F; age 56 a +/- 11 a) diagnosed ""lung field shadow"" underwent the lung focus and mediastinal lymph nodes resection. As the golden standard, pathologic diagnosis was used to evaluate the role of preoperative 99mTc-MIBI SPECT. RESULTS: The sensitivity, specificity, and accuracy of 99mTc-MIBI SPECT were 93%, 50%, and 86%, respectively in lung cancer and 81%, 95%, and 88%, respectively in mediastinal metastasis lymph node. The results were also better than those of chest scan with CT. CONCLUSION: The 99mTc-MIBI SPECT is a useful and noninvasive method for diagnosing lung cancer and predicting mediastinal metastasis lymph nodes, which will guide the surgeon to resect the mediastinal metastasis lymph nodes.